2022
DOI: 10.1016/j.jvs.2021.07.120
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter European real-world utilization of VasQ anastomotic external support device for arteriovenous fistulae

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The most common reason for hemodialysis was diabetic nephropathy (Table 1 ). This correlates with the data from the literature sources [ 9 , 10 ]. In all patients, the AVF procedure was performed on the non-prominent arm.…”
Section: Discussionsupporting
confidence: 90%
“…The most common reason for hemodialysis was diabetic nephropathy (Table 1 ). This correlates with the data from the literature sources [ 9 , 10 ]. In all patients, the AVF procedure was performed on the non-prominent arm.…”
Section: Discussionsupporting
confidence: 90%
“…A lot of research has been conducted on improving vascular access outcomes, but no large breakthroughs have taken place since the introduction of the AVF. Most recent innovations focus on optimizing local hemodynamics, but show limited benefits [18], [19]. The supraphysiological flow causing complications remains ever-present, whereas dialysis is only performed for a limited number of hours per week [6].…”
Section: An Implantable Magnetic Drive Mechanism For Non-invasive Art...mentioning
confidence: 99%
“…Recent studies demonstrated the device is safe, and reported improved functional patency for AVFs created using the VasQ TM as compared to AVFs created with conventional surgery. [6][7][8][9][10][11] However, the effect of the device on hemodynamic conditions and its role in regularizing the blood flow have yet to be adequately assessed. We have recently shown that coupling non-contrast enhanced magnetic resonance imaging (MRI) and highresolution CFD provides a promising approach 12 to investigate AVF morphology and hemodynamics, possibly identifying critical hemodynamic conditions that may contribute to AVF remodelling after surgery.…”
Section: Introductionmentioning
confidence: 99%